In Vitro Anticancer Properties of Linamarin Controlled Release From Biodegradable Poly-Lactic Co-Glycolic Acid Nanoparticle - Alfourjani, Wedad Ashour (2005)
There are many interests in finding new chemotherapeutic agents for cancer. The current work involved screening of linamarin as the therapeutic agent on different cancer cells, as no such study has been performed previously. Improved bioavailability and delivery of the linamarin to the targeted tumour cells can be engineered by proper selection of its carrier. There are many advantages of choosing biodegradable nanoparticles as a drug carrier. These include an improved bioavailability and efficacy of the drug. It also offers a controlled release mechanism in which the activity of the drug can be prolonged at the affected sites. Besides, the biodegradability character of the carrier means these particles are easily dissolved in the system without exerting any side effects to the body. The present study investigated fabrication of linamarin encapsulation into biodegradable nanoparticles to kill cancer cells. The present study was initiated with an investigation of the toxic effect of linamarin on cancer cells and their cell cycles. The in vitro study on the effect of linamarin was performed on two tumour cell lines, HeLa (cervical tumour cell line) and CAOV3 (ovarian tumour cell line). The cytotoxicity of linamarin was determined by the MTT assay. Both cell lines showed significant cell death when exposed to linamarin with the IC50 values well within the efficacious limit (IC50 of 30 mglml and 58 mglml for HeLa and CAOV3 cell lines, respectively, when exposed to pure linamarin). This result indicated that linamarin has the potential as a for drug candidate for cancer treatment. The subsequent cell cycle analysis performed by flow cytometry to determine the arrested point of linamarin within the cell cycle. Results showed significant effect of linamarin on the G1 phase of the cell cycle. In other words, a significant number of cells were being arrested in the G1 phase. However, no significant effect was observed on the S and G2-M stage of the cell cycle stage after treatment with the linamarin for 24 hours. The second part of the study was on fabrication of biodegradable linamarin loaded nanoparticles. Poly (lactic-co-glycolic acid) (PLGA) was chosen as the polymeric material of the nanoparticles. The water-in-oil-in-water emulsification process was the method of choice for the encapsulation of linamarin inside polymeric particles. The linamarin nanoparticles based on two different mole fraction of PLGA copolymer (50150 and 85150 of lactic acidglycolic acid, respectively) were successfully fabricated using water-in- oil-in-water double emulsion extractionlevaporation technique. The SEM analysis on the morphologies of the nanoparticles showed the particles are spherical in shape with porous surface structure and well within nano-scale in size. A preliminary investigation on in vitro drug (linamarin) release was also carried out. The in vitro drug (linamarin) release was characterised by an initial burst and incomplete dissolution of the drug. When decreasing the polymer/drug ratio, the release appeared more controlled and prolonged up to 8hr. It can be concluded that nanoparticles prepared by water-in-oil-in-water emulsification followed by solvent evaporation is a good potential for a controlled released-drug carriers for linamarin.